Evaluating bone quality and asymmetrical aplasia of the thoracic vertebral body in Lenke 1A adolescent idiopathic scoliosis using hounsfield units - Chen, Taiqiu; Hu, Wenjun; Peng, Yan; Li, Yong; Qiu, Jincheng; Qiu, Xianjian; Li, Pengfei; Li, Shaoguang; Liang, Anjing; Gao, Wenjie; Huang, Dongsheng (Frontiers in Surgery, 2022)
Study Design. Retrospective analysis. Objective. To evaluate bone quality and investigate asymmetrical development of the thoracic vertebral body in adolescent idiopathic scoliosis (AIS) based on Hounsfield unit (HU) measurements obtained from computed-tomography (CT) scans. Summary of Background Data. HU value demonstrated higher reliability and accuracy than the traditional method, indicating that they could be used to individually evaluate and effectively assess the bone quality of every vertebra in the CT films. Methods. Total 30 AIS patients classified as Lenke Type 1A and 30 paired controls were included in this study. Regions of interest for HU value were measured on three horizontal images of the thoracic vertebrae. HU measurements of the whole vertebral body in each vertebra were obtained. Using HU value, we separately measured the concave and convex sides of each vertebral body in patients’ group, as well as within the left and right sides in controls. Results. In controls, the mean HU value of T1-T12 thoracic vertebral bodies was 240.03±39.77, with no statistical differences among different levels. As for AIS patients, in the structural curve, the apical region had a significantly lower HU compared with the other regions, and asymmetrical change was found between the concave and convex sides, most significantly in the apical region. In the non-structural curve, the average HU value was 254.99±44.48, and no significant difference was found either among the different levels of vertebrae or between the concave and convex sides. Conclusions. Abnormal and asymmetrical changes in bone quality of the thoracic vertebral body in patients with Lenke 1A AIS were indicated. Low bone quality in the convex side of the structural curve indicated stronger internal fixation in surgery to correct the deformity.